An exploratory model of water and solute excretion in animals - Letts, Robyn (My University, 2022)
"What goes in must go out" is the dictum of mass balance, and excretion. All animals need to take in nutrients and excrete excess and waste products; how they achieve this depends on the capacity of their individual excretory systems and their tolerance to survive in a particular environment. Avoiders seek refuge from extreme or highly fluctuating environmental conditions, conformers are able to follow the environment, while regulators keep their internal environment in terms of volume and osmolarity approximately constant. A systems’ analysis of excretion was performed across the animal spectrum. Taking inspiration from comparative biology, a bottom-up, exploratory and indeed, evolutionary approach to modelling was followed where the multiple iterations each represent an increasing level of structural complexity to meet increasing functional constraints, just as in the biology it aims to imitate. Acknowledging that results need to be considered with the high level of abstraction in mind; interest lies in modes of behaviour and signature trends rather than point prediction. Nonetheless, this has led to the emergence of a number of contributions and hypotheses in the field of renal physiology, worthy of further research. It was found that, no matter the complexity of animal being considered, a single continuously-stirred tank satisfactorily provides the core of the model. The mean residence time of the tank alone was found to determine sensitivity of the response to disturbances in water and solute inflow, implying a need for more sophisticated excretory control in a volume- and osmo-regulating animal with a smaller mean residence time compared to that with a higher mean residence time, simply based on size relative to flow. Through similar argument, it is suggested that higher than expected infant drug sensitivity is due to reduced mean residence time when compared with older children and adults, and not necessarily organ immaturity. Simple volume or pressure feedback on the outflow of the tank was found to be sufficient in describing volume regulation at the level of cells; and pressure diuresis and natriuresis in primitive animals such as the hagfish through to long-term arterial pressure control in sophisticated mammals, emphasising its inherent utility. In addition, a possible explanation for the exponential shape of the renal urinary output or renal function curve in humans is suggested. Unintentionally, simply considering increasing regulatory requirements of excretion and iteratively building in requisite structure on the tank outflow, led to the development of a multiple-separator, series-parallel model that has clear analogies with that of differential intrarenal blood flow and nephron heterogeneity as present in the kidneys of birds and mammals, incidentally the only animals able to elucidate concentrated urine. Interestingly, variable flow between parallel separators and distal series water reabsorption have direct renal analogues; i.e. vascular and tubular receptors for antidiuretic hormone, respectively. Similar trends in electrolyte imbalance and volume- and osmo-dysregulation that are exhibited in the syndrome of inappropriate antidiuresis and exercise-associated-hyponatremia were achieved. In addition, a hypothesis regarding the proposed action of loop diuretics was made based on model findings; that a shunt in flow towards the diluting branch of the parallel separator arrangement causes the same trend in volume depletion and electrolyte imbalance (i.e. potassium-losing). In addition, the developed tank-separator-recycle architecture (as present in the kidneys of birds and mammals) provides a mechanism for achieving energetically "passive" urine concentration; i.e. one in which all energy is derived externally from blood pressure. Real-time visualisation of blood flow to cortical and medullary regions of human kidneys under administration of both antidiuretic hormone and a loop diuretic with non-invasive phase-contrast MRI or ultrasound is suggested to provide falsifiability for the proposed contribution of flow redistribution to the urine concentrating mechanism in mammals.
This thesis submitted in fulfilment of the requirements for for the degree of Doctor of Philosophy to the Faculty of Engineering and Built Environment, School of Electrical and Information Engineering, University of the Witwatersrand, Johannesburg, 2022